2016
DOI: 10.1152/ajplung.00301.2015
|View full text |Cite
|
Sign up to set email alerts
|

γ-Tocopherol supplementation of allergic female mice augments development of CD11c+CD11b+dendritic cells in utero and allergic inflammation in neonates

Abstract: γ-Tocopherol increases responses to allergen challenge in allergic adult mice, but it is not known whether γ-tocopherol regulates the development of allergic disease. Development of allergic disease often occurs early in life. In clinical studies and animal models, offspring of allergic mothers have increased responsiveness to allergen challenge. Therefore, we determined whether γ-tocopherol augments development of allergic responses in offspring of allergic female mice. Allergic female mice were supplemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 93 publications
0
47
0
Order By: Relevance
“…The risk for allergic disease in humans is associated with in utero and early exposures to environmental factors 5 . In animal studies, we and others have reported that offspring from allergic mothers are predisposed to allergic lung responses to suboptimal allergen doses 615 . It is not known whether offspring of allergic mother mice have increased responsiveness to sensitization to food allergens and food-induced anaphylaxis.…”
Section: Introductionmentioning
confidence: 90%
“…The risk for allergic disease in humans is associated with in utero and early exposures to environmental factors 5 . In animal studies, we and others have reported that offspring from allergic mothers are predisposed to allergic lung responses to suboptimal allergen doses 615 . It is not known whether offspring of allergic mother mice have increased responsiveness to sensitization to food allergens and food-induced anaphylaxis.…”
Section: Introductionmentioning
confidence: 90%
“…In mice prone to allergic disease, supplementing allergic mothers (at the time of mating) with α -tocopherol was enough to inhibit the pup allergic responses [ 67 ], while γ -tocopherol supplementation amplified pup responses to allergens [ 70 ].…”
Section: Exogenous Antioxidants and Human Healthmentioning
confidence: 99%
“…These differences in allergic response development exerted by α - or γ -tocopherol supplementation are dependent from their modulation of eosinophils and CD11c + CD11b + dendritic cell numbers in the lungs; α -tocopherol reduced both the cellular species, without affecting the number of CD11c + CD11b − regulatory dendritic cells, while γ -tocopherol increased both eosinophils and CD11c + CD11b + dendritic cells [ 69 , 70 ].…”
Section: Exogenous Antioxidants and Human Healthmentioning
confidence: 99%
“…On the other hand, γ-tocopherol supplementation exerted an opposite response in the same model. In vivo supplementation of γ-tocopherol at 250 mg/kg diet in allergic female mice resulted in a higher number of lung eosinophils, a higher number of lung CD11c + CD11b + DCs, and higher levels of lung lavage CCL11 in the offspring [ 79 ].…”
Section: Vitamin E and Immune Cellsmentioning
confidence: 99%